Greater Anis (Crotophaga major) Commensal Foraging with Freshwater Fish in the Pantanal Floodplain, Brazil - Ubaid, Flavio Kulaif (Wilson Ornithological Soc, 2011)
Foraging associations between birds and other groups of animals have been widely reported in the literature. I report the first observation of a foraging tactic involving a flock of Greater Ani (Crotophaga major), which deliberately followed fish along an artificial ditch in the Pantanal wetlands, feeding on animals flushed by the movement of the vegetation on the ditch banks. Further observations of the feeding behavior and foraging tactics of Greater Anis are necessary to ascertain if this type of behavior is a frequent event or merely sporadic. Received 22 June 2010. Accepted 11 October 2010.